P40 as a Basal Cell Marker in the Diagnosis of Prostate Glandular Proliferations: A Comparative Immunohistochemical Study with 34betaE12. (8th March 2015) - Brustmann, Hermann
Abstract : Immunohistochemistry is important for the accurate diagnosis of basal cells in atypical glandular proliferations of the prostate. p40, an isoform of p63, may be an adjunct to a marker panel in this setting. Biopsies of 68 patients were analyzed by immunohistochemistry using antibodies to 34betaE12 and p40. Basal cell staining was classified as negative, partial (<60%), or diffuse (≥60%); irregular staining was defined as discordant staining patterns. In acinar proliferations (N = 41 ), partial staining for both markers was seen in 42%, and diffuse staining in 46% of reactive cases. An irregular reactivity was noted in one case only (2%). Finally, these lesions were signed out as benign. Acinar proliferations negative for both markers and limited amount of glands (≤4) were termed atypical small acinar proliferations (ASAP). Out of six PIN lesions two cases showed partial, three cases showed diffuse reactivity for both markers, and one case was stained irregular. All cases diagnosed as prostate carcinomas (N = 20 ) had no evidence of basal cell staining for neither of the markers. p40 expression is closely correlated to 34betaE12 with respect to demonstration of basal cells of prostate glands and may provide further information on the dignity of glandular proliferations of the prostate.